Gelar Mokole (Raja) di Kerajaan Konawe: Prosedur Pengangkatan - Basrin Melamba; Raemon . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This study describes about the procedure of the King appointment that has title as Mokole of Konawe Kingdom in the past. The searching of information is done through the literature study from the several of written sources. The objectives of this study is to realign the history of the appointment of mokole in Konawe Kingdom, so it can be used as reference for efforts to restore the identity sovereignty of Konawe Kingdom through the mechanism of selection and appointment of Mokole or king based on osara, hohowino, and the terms of Mokole appointment that is standard and accordance with sara owoseno wonua. Keywords: procedure, appointment, mokole, Konawe kingdom